Qualitative inquiry into perceptions of HIV pre-exposure prophylaxis among people who inject drugs living with hepatitis C in Seattle, WA, USA - Michael P. Barry; Elizabeth J. Austin; Elenore P. Bhatraju; Sara N. Glick; Joanne D. Stekler; Elyse L. Tung; Ryan N. Hansen; Emily C. Williams; Alexander J. Gojic; Eleanor I. Pickering; Judith I. Tsui (BMC, 2022)
Abstract Background The incidence of HIV among persons who inject drugs (PWID) in the USA has been increasing since 2014, signaling the need to identify effective ways to engage PWID in HIV prevention services, namely pre-exposure prophylaxis (PrEP). Yet, the uptake of PrEP in this population is minimal compared to other populations at risk of HIV acquisition. In this work, we sought to explore knowledge, attitudes, and perspectives of PrEP acceptability among PWID. Methods In the context of a pilot study to explore the acceptability of pharmacy-based hepatitis C virus (HCV) treatment, we conducted semi-structured interviews (n = 24) and focus groups (n = 4, 16 participants) with people who were living with HCV and reported active injection drug use (≤ 90 days since last use). Participants were asked open-ended questions about their familiarity with and motivation to use PrEP. As part of a sub-analysis focused on PrEP, qualitative data were analyzed using a Rapid Assessment Process, where three coders used structured templates to summarize qualitative data and iteratively reviewed coded templates to identify themes. Participants also completed short quantitative questionnaires regarding drug use history and attitudes toward health concerns. Results Forty-seven percent of participants expressed having little or no concern regarding HIV acquisition. Targeted analyses focused on HIV prevention identified three themes, which help characterize behavioral determinants of nonadoption. First, knowledge of PrEP was limited among PWID and influenced by infrequent open community discussions around HIV risk. Second, PWID perceived sexual behaviors-but not injection drug use-as a motivator for HIV risk prevention. Finally, PWID identified many individual and environmental barriers that hinder PrEP uptake. Conclusion Among PWID, PrEP is rarely discussed and concerns about the feasibility of using daily PrEP are common. Taken with the prevalent perception that drug use is not a high risk for HIV acquisition, our findings point to opportunities for public health work to target PrEP education to PWID and to leverage other successful interventions for PWID as an opportunity to provide PrEP to this vulnerable population.